Strategic database marketing. - Hughes, Arthur Middleton, ....- (New York : McGraw-Hill, 2006)
Pt. 1. What Is Database Marketing? Introduction 1. Strategic Database Marketing: An Overview 2. "The Vision Thing" Pt. 2. Strategy Development 3. Lifetime Value: The Criterion of Strategy 4. Strategy: How to Build Profits with a Database 5. Building Profits with Recency, Frequency, Monetary (RFM) Analysis 6. Using Customer Profiles in Marketing Strategy 7. Building Relationships with Surveys 8. How Modeling Helps Build Profits 9. Strategy Verification: Testing and Control Groups Pt. 3. Profiting by Experience 10. Database Strategy for Retailers 11. Packaged Goods Databases: Don't Lose Your Shirt 12. Business-to-Business Database Marketing 13. Financial Services Database Marketing 14. Why Databases Fail 15. Database Types that Succeed 16. Database Marketing and the Internal Struggle for Power
Subtitle on the cover: The Masterplan for Starting and Managing a Profitable, Customer-Based Marketing Program
Keywords: Databasemarketing